An unreported case of intraoperative frozen section diagnosis of a sclerosing stromal tumor of the ovary- A report with a review - Pavithra Ayyanar; Mukund N. Sable; Pruthwiraj Sethi; Niraj Prasad; Pritinanda Mishra (Wolters Kluwer Medknow Publications, 2024)
Sclerosing stromal tumor is a benign sex cord-stromal tumor, that commonly occurs in the second and third decades of age. Intraoperative diagnosis of this entity poses a great challenge because of the rare occurrence and can mimic malignant lesions. A 15-year-old female presented with a right ovarian mass. Serum markers were within normal limits. The radiological evaluation showed a large heterogeneously enhancing solid cystic abdominopelvic mass of size 16 × 14 × 9 cm with non-visualization of both ovaries separately and a few areas of calcification with mild ascites. An open cystectomy was performed. A part of the cyst wall was sent for an intraoperative frozen section. It was reported as sclerosing stromal tumor, and the post-operative specimen also confirmed the same. Areas of calcification and ossification were also identified as additional findings. We reported this case because of the uncommon occurrence, highlighting additional histological features, and also did a literature review, especially focussing on the intra-operative diagnosis.